Contribution of Agroforestry to Farmers' Income and Welfare in Jujun Village Kerinci Regency - Achmad, Eva; Ulfa, Maria; Fazriyas; Tamin, Rike Puspitasari (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2026)
Jujun Village is located in Kerinci Regency and is one of the Integrated Laboratory Villages fostered by Jambi University. Jujun Village is known to have the largest area in Keliling Danau District, and most of its residents work as farmers and have cultivated land. The agroforestry cropping pattern approach has begun to be carried out by the community, especially since the benefits of agroforestry for the community were explained again from an ecological and economic perspective. In the journey of the agroforestry system in Jujun Village, it is necessary to know what its contribution is to community income. Specifically, this study seeks to analyze the contribution of agroforestry to the income and welfare of farmers in Jujun Village. This study ran for 8 months from April to November 2024 and was carried out in Jujun Village. This study uses quantitative and qualitative descriptive methods with an analysis focused on farmers' income and welfare. The results of the study show that farmers have implemented agroforestry on their land with a combination of various types of agricultural and forestry crops. The analysis carried out provides an overview of the contribution of agroforestry to farmers' income in general with varying levels of contribution. The average contribution of agroforestry to total farmer income is 51.97%. The average contribution of agroforestry to total farmer income is 51.97%. Meanwhile, the level of farmer welfare ranges from almost poor (33.33%), sufficient (26.67%), to decent living (23.33%).